Relazione, comunità, contesti. Note sul vincolo relazionale - Bombelli, Giovanni (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
This contribution aims to offer some initial functional notes to reflect around the nexus among the idea of “relationship”, community horizon and contexts. Moving from what could be defined as the “relationship question” and through an anthropological-philosophical approach, the essay addresses the theoretical figures of desire and language. Subsequently, the analysis focuses on some aspects that seem to inform the “structure” of the relationship, identifying its syntax and semantics especially with regard to the community dimension. In particular, the thirdness of relationship is discussed both in the pragmatic and juridical-institutional level. Fi-nally, the contribution will consider some of the profiles that characterise today’s technological and socio-cultural contexts, in order to re-read the complexity of the relational dimension The analysis will conclude by sketching out two points underly-ing the itinerary presented here.